2012
DOI: 10.1002/ejic.201200360
|View full text |Cite
|
Sign up to set email alerts
|

Complex‐Formation Ability of Salicylaldehyde Thiosemicarbazone towards ZnII, CuII, FeII, FeIII and GaIII Ions

Abstract: The stoichiometry and stability of copper(II), zinc(II), iron(II)/ (III) and gallium(III) complexes of salicylaldehyde thiosemicarbazone (STSC, H 2 L) have been determined by pH potentiometry, UV/Vis spectrophotometry, and 1 H NMR and EPR spectroscopy in aqueous solution (with 30 % DMSO), together with the characterization of the proton dissociation processes. Mono-and bis-ligand complexes in different protonation states were identified for Fe II , Fe III and Ga III , whereas Cu II and Zn II ions only form com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
91
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(114 citation statements)
references
References 41 publications
14
91
0
9
Order By: Relevance
“…The acid-base properties of STSC have already been studied in detail in our previous work [25], and the pK a values determined here are in good agreement with the published data ( considerably higher compared to those of the α(N)-pyridyl TSCs ( Table 1). …”
Section: Complex Formation Of Stsc With Vanadium(iv/v) Ions and Cytotsupporting
confidence: 91%
See 2 more Smart Citations
“…The acid-base properties of STSC have already been studied in detail in our previous work [25], and the pK a values determined here are in good agreement with the published data ( considerably higher compared to those of the α(N)-pyridyl TSCs ( Table 1). …”
Section: Complex Formation Of Stsc With Vanadium(iv/v) Ions and Cytotsupporting
confidence: 91%
“…As expected, the methyl groups on the terminal nitrogen of the α-pyridyl TSCs increase the logD 7.4 value compared to that of the reference compound Triapine [25].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore the salicylidene compounds might prefer harder metals than the picolinylidene derivatives [110]. A study comparing the stability of several metal complexes formed by the N4 unsubstituted salicyl-and pyridyl-carbaldehyde TSCs supports this general trend [111]. The different chelators might not only influence the stability of complexes formed with diverse metal ions, but also their redox properties.…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…Low aqueous solubility of TSCs is a common feature, that explains the limited number of studies in aqueous solution reported so far. 43,44,45,46,47 From the other side aqueous solubility has influence on a compound's bioavailability through solubility-limited absorption, but is important for validation of in vitro antiproliferative activity assays. 48 We reported recently on the first proline-TSC hybrids (L-and D-Pro-FTSC) and their copper(II) complexes.…”
Section: Introductionmentioning
confidence: 99%